Drivers and barriers of vaccine acceptance among pregnant women in Kenya. Issue 10 (2nd October 2020) - Otieno, Nancy A.; Otiato, Fredrick; Nyawanda, Bryan; Adero, Maxwel; Wairimu, Winnie N.; Ouma, Dominic; Atito, Raphael; Wilson, Andrew; Gonzalez-Casanova, Ines; Malik, Fauzia A.; Widdowson, Marc-Alain; Omer, Saad B.; et al.
ABSTRACT: Maternal vaccination coverage remains suboptimal globally and is lowest in low- and middle-income countries. Attitudes toward maternal vaccines have been characterized in middle-high income settings, however data from African countries are limited. We assessed drivers and barriers of vaccine acceptance among pregnant women in Kenya. We conducted a cross-sectional survey among pregnant women aged 15–49 y. We enrolled a convenience sample of women presenting for antenatal care at seven health-care facilities in four diverse counties (Nairobi, Mombasa, Marsabit, Siaya) of Kenya and from the community in two counties (Nairobi, Siaya). We described frequencies of socio-demographic characteristics of participants and their knowledge, attitudes, and beliefs regarding maternal vaccination. We enrolled 604 pregnant women with a median age of 26.5 y, of whom 48.2% had primary education or less. More than 95% agreed that maternal vaccines are "important for my health" and that getting vaccinated is "a good way to protect myself from disease". The most commonly cited reason in favor of maternal vaccination was disease prevention (53.2%). Fear of side effects to mother/baby (15.1%) was the most frequently reported potential barrier. Influenza vaccine is not in routine use in Kenya; however, 77.8% reported willingness to accept influenza vaccination during pregnancy. Maternal vaccination is well accepted among Kenyan pregnant women. We identified the provision of adequate vaccine information and addressing safety concerns as opportunities to improve maternal vaccine uptake. The expressed willingness to receive a vaccine not currently in routine use bodes well for implementation of new maternal vaccines in Kenya.